Discrete geometry for computer imagery : 21st IAPR International Conference, DGCI 2019, Marne-la-Vallée, France, March 26-28, 2019, Proceedings /: 21st IAPR International Conference, DGCI 2019, Marne-la-Vallée, France, March 26-28, 2019, Proceedings. (2019) - Unknown
No abstract available